2019
DOI: 10.1038/s41386-019-0319-6
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the FKBP5 gene in association with FKBP5 genotypes, childhood maltreatment and depression

Abstract: DNA methylation of the FKBP5 gene is assumed to alter FKBP5 expression and hence the synthesis of the FK506 binding protein 51, a central element of a genomic negative feedback loop for glucocorticoid receptor signaling. The present study aimed to replicate and extend previously reported influences of FKBP5 genotypes, childhood maltreatment and depression on methylation levels of five CpG sites in intron 7 of the FKBP5 gene in a large population-based sample. Besides the single nucleotide polymorphism (SNP) rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 42 publications
(93 reference statements)
8
27
1
Order By: Relevance
“…This effect was more recently replicated by Tozzi and colleagues 48 who also reported that childhood maltreatment was associated with lower FKBP5 methylation among those with the T risk allele of the rs1360780 SNP. In contrast, Harms et al 49 found significant positive associations between stress in childhood and methylation of FKPB5 in young adulthood using a prospective longitudinal design, and a number of studies did not find significant associations among childhood maltreatment and FKBP5 methylation 50 53 , or moderation by FKBP5 risk allele 50 , 51 .…”
Section: Resultsmentioning
confidence: 92%
“…This effect was more recently replicated by Tozzi and colleagues 48 who also reported that childhood maltreatment was associated with lower FKBP5 methylation among those with the T risk allele of the rs1360780 SNP. In contrast, Harms et al 49 found significant positive associations between stress in childhood and methylation of FKPB5 in young adulthood using a prospective longitudinal design, and a number of studies did not find significant associations among childhood maltreatment and FKBP5 methylation 50 53 , or moderation by FKBP5 risk allele 50 , 51 .…”
Section: Resultsmentioning
confidence: 92%
“…When looking at the chaperone FKBP5, the evidence for a possible association of methylation patterns with maltreatment is even less straightforward, with some studies showing associations of childhood adversity with FKBP5 methylation [ 19 , 33 , 54 ], while others reporting negative results [ 55 , 56 ]. Such divergent findings may, in part, reside in the fact that the type of traumatic experience needs to be considered, i.e., early versus late, single incident versus repetitive traumatization, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation concerns the lack of investigation of polymorphic variation of the receptor coding gene [ 64 ], since the impact of FKBP5 methylation on psychopathology has been reported to be related to SNP variants within FKBP5 (e.g. [ 56 , 65 ]). Fourth, it needs to be taken into consideration that childhood trauma, psychopathology and empathy measures relied on self-report.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been associated with depression previously (Starnawska et al, 2019). The other CpGs on the significant list was cg26495008 and cg10913456 , both in the FKBP Prolyl Isomerase 5 ( FKBP5 ) gene, previously associated with childhood maltreatment and depression (Klinger-König et al, 2019; Mehta et al, 2013); and risk of PTSD (Binder et al, 2008; Pape et al, 2018). The role of other significant genes detected by ML include: Nuclear Factor Kappa B Subunit 1 ( NFKB1 ), which has been associated with personality disorders (Gescher et al, 2018); Interleukin 4 ( IL4 ), which has been associated with PTSD (Smith et al, 2011); Nuclear Receptor Subfamily 3 Group C Member 1 ( NR3C1 ), previously associated with emotion dysregulation, psychopathology (Cicchetti & Handley, 2017), depression (Borçoi et al, 2020; Efstathopoulos et al, 2018), and risk of PTSD (Schechter et al, 2015; Vukojevic et al, 2014); and Nuclear Factor Of Activated T Cells 1 ( NFATC1 ), which has been previously associated with PTSD and depression (Kuan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%